On the corrosion, stress corrosion and cytocompatibility performances of ALD TiO2 and ZrO2 coated magnesium alloys. (January 2022) - Peron, M.; Bertolini, R.; Cogo, S.
Abstract: Magnesium alloys are increasingly studied as materials for temporary implants. However, their high corrosion rate and susceptibility to corrosion-assisted cracking phenomena, such as stress corrosion cracking (SCC), continue to prevent their mainstream use. Recently, coatings have been considered to provide an effective solution to these issues and researchers have focused their attention on Atomic Layer Deposition (ALD). ALD stands out as a coating technology due to the outstanding film conformality and density achievable, and has shown encouraging preliminary results in terms of reduced corrosion rate and reduced SCC susceptibility. Here, we contribute to the ongoing interest in ALD-coated Mg alloys, providing a comprehensive characterisation of the effect of 100 nm thick ALD TiO2 and ZrO2 coatings on the corrosion behaviour and SCC susceptibility of AZ31 alloy. Moreover, we also investigate the effect of these coatings on the induced biological response. Our results suggest that the ALD coatings can improve the corrosion and SCC resistance of the Mg alloy, with the ZrO2 ALD coating showing the best improvements. We suggest that the different corrosion behaviours are the cause of the cytocompatibility results (only the ZrO2 ALD coating was found to meet the demands for cellular applications). Finally, we leverage on considerations about the coatings' wettability, electrochemical stability and surface integrity to justify the different results.